AN ANALYSIS OF CODE MIXING BY TWITTER USERS OF UNIVERSITY STUDENTS - Pangeran M Faqih Syafaat; Eliwarti '; Novitri M (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This descriptive research aimed to find out the forms of code mixing by twitter users of university students, The research used Bokamba (1989) theory to determine the forms of code mixing. There are six forms of code mixing such as morpheme, word, phrase, hybrid, clause and idiom. The research was conducted at Riau University from May-June 2016. it was conducted in eight different spots. They are The Faculty of Economy, Faculty of Social and Politics, Faculty of Teachers Training and Education, Faculty of Fisheries and Marine, Faculty of Agriculture, Faculty of Law, Faculty of Mathematics and Science and the last is The English Department. The data and instruments used researcher’s twitter account and tweets that inserted code mixing. Researcher’s twitter account follows 286 twitter accounts that among of those are 130 Riau University student accounts. The Population of research is 130 Riau University student accounts. The researcher used purposive sampling technique. The sample is 61 Riau University student accounts because they have particular characteristics to be sampled such as their tweets used code mixing and they are university students. In addition, they also agreed to take part in this research. The result of the data showed that words was the majority of the data with 42 data then followed by morpheme with 39 data and phrase has 14 data while the fewer of data is hybrid is three (3), clause is one (1) and the last is idiom has four (4) data.Key words: Sociolinguistics, Code mixing, Twitter